Study of The Linear Attenuation Coefficent for Gamma Rays and Beta Rays of Epoxy Polymer Reinforced with Different Ratios of Lead Oxide and Manganese Oxide - Elhams, Amjad Moussa; Ben Yazid, Moftah Ali (The 1st International Conference On Basic Sciences & Its Applictionss, 2024)
In this research paper, the linear attenuation coefficient for gamma rays and beta particles (radiation attenuation) was studied using epoxy polymer samples with a hardener (210 A+B) and added red lead oxide with a purity of 99.97% and manganese oxide with a purity of 99.97% in weight percentages (0%, 10%, 20%, 30%, 40%, 50%, 60%). The linear attenuation coefficient μ for both gamma rays and beta particles was studied using a radioactive radium (Ra) source that emits gamma rays with an energy range of (0.416 - 0.478) MeV and a radioactive activity, and a strontium (Sr) source that emits negative beta particles with an energy of 0.546 MeV and a radioactive activity of 37 KBq. A Geiger-Muller counter system was used to study the attenuation coefficient for all samples. The experimental results showed that the samples containing lead oxide and manganese oxide, especially at higher percentages (40% - 60%), had a high linear absorption coefficient for gamma rays ((1.3/cm for the lead oxide sample and 0.95/cm for the manganese oxide sample). The measurements also showed that the linear absorption coefficient for beta rays is greater than the linear absorption coefficient for gamma rays for the same mixing ratios. The study also showed that the linear absorption coefficient for samples containing lead oxide is generally higher than the linear absorption coefficient for samples containing manganese oxide. The highest value of the linear absorption coefficient was obtained at a ratio of 60% for both lead oxide and manganese oxide.